Agriculture and Development in the Wake of the Arab Spring - Eckart Woertz (Revue Internationale de Politique de Développement)
This paper analyses the role of agriculture in the political economy of the Middle East and North Africa (MENA). It outlines agriculture’s relative contribution to development and employment, shows linkages with food security policies, and discusses possible future scenarios. Agriculture’s role in the economies of MENA is limited nowadays, but its contribution to employment is still substantial. In many countries it is at the heart of the region’s water crisis as it withdraws about 80 per cent of water resources. Agricultural constituencies have played an important role in sociopolitical transformations of the region. Populist regimes tried to win them over—as support base—with land reforms enacted in the 1950s and 1960s. Since the 1980s these earlier reforms have been pushed back and the sector has been liberalised under bureaucratic-authoritarian reform coalitions. In other countries, such as Saudi Arabia, extensive production subsidies have been maintained. The MENA region is the largest cereal importer in the world and its governments regard this dependency as a strategic liability. However, the quest for self-sufficiency has proven to be elusive in the light of natural constraints and population growth. The major challenge in MENA is not macro food security or lack of calories, but deficiencies of micronutrients such as vitamins and iron and a lack of accessible food for the poor. Hence, inclusive growth, rural livelihood strategies, and political participation will be crucial for food security in MENA.